2022
DOI: 10.3390/microorganisms10020433
|View full text |Cite
|
Sign up to set email alerts
|

Two-Drug Regimens for HIV—Current Evidence, Research Gaps and Future Challenges

Abstract: During the last 30 years, antiretroviral treatment (ART) for human immunodeficiency virus (HIV) infection has been continuously evolving. Since 1996, three-drug regimens (3DR) have been standard-of-care for HIV treatment and are based on a protease inhibitor (PI) or a non-nucleoside reverse transcriptase inhibitor (NNRTI) plus two nucleoside reverse transcriptase inhibitors (NRTIs). The effectiveness of first-generation 3DRs allowed a dramatic increase in the life expectancy of HIV-infected patients, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…This study demonstrated non-inferiority at 48 weeks between the 2D and 3D regimens (88.9% vs. 92.7%) [6]. Despite these earlier studies, many concerns remained about the durability of the regimens, the inability to utilize them in certain populations such as pregnant women or those with tuberculosis, the concern about adequate suppression of viral reservoirs, the paucity of studies in naïve patients, and some conflicting data that did not show non-inferiority [3].…”
Section: Protease Inhibitorbased Regimensmentioning
confidence: 67%
See 2 more Smart Citations
“…This study demonstrated non-inferiority at 48 weeks between the 2D and 3D regimens (88.9% vs. 92.7%) [6]. Despite these earlier studies, many concerns remained about the durability of the regimens, the inability to utilize them in certain populations such as pregnant women or those with tuberculosis, the concern about adequate suppression of viral reservoirs, the paucity of studies in naïve patients, and some conflicting data that did not show non-inferiority [3].…”
Section: Protease Inhibitorbased Regimensmentioning
confidence: 67%
“…Initial attempts starting around 2000 combined boosted protease inhibitors(PIs) and non-nucleoside reverse transcriptase inhibitors (NNRTIs) but still showed higher levels of toxicity and/or lower efficacy than triple-drug regimens and led to studies simplifying to a regimen containing a boosted PI and an NRTI [3]. Such switch studies included the open-label GARDEL study, which enrolled 416 patients naive to therapy comparing boosted lopinavir (LPV/r) and lamivudine (3TC) to LPV/r and 2NRTIs [4], and the ATLAS-M study [5], comparing boosted atazanavir (ATV/r) and 3TC in 266 virologically suppressed patients to ATV/r and 2NRTIs; both studies showed non-inferiority by intent to treat analysis.…”
Section: Protease Inhibitorbased Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The aims are to limit cumulative lifetime drug exposure along with associated adverse events related to these drugs while limiting the risk of drug-drug interaction. [7][8][9] Despite these advantages, a small percentage of PLWHA on dual therapy experience virological failure. [10][11][12] We can hypothesize that these poor outcomes might be partly associated with inadequate drug exposure and therapeutic drug monitoring (TDM) is then an additional tool in management of PLWHA, which can clarify patients' drug exposures, enabling rational adjustment of their medications or adherence interventions.…”
Section: Introductionmentioning
confidence: 99%
“…This dual therapy is a single tablet, pill burden reducing strategy, which avoids the use of nucleos(t)ide reverse transcriptase inhibitors and boosted protease inhibitors in non‐HBV coinfected patients 6 . The aims are to limit cumulative lifetime drug exposure along with associated adverse events related to these drugs while limiting the risk of drug–drug interaction 7–9 . Despite these advantages, a small percentage of PLWHA on dual therapy experience virological failure 10–12 .…”
Section: Introductionmentioning
confidence: 99%